PIRCHE-II Is Related to Graft Failure after Kidney Transplantation - Geneugelijk, Kirsten; Niemann, Matthias; Drylewicz, Julia; van Zuilen, Arjan D.; Joosten, Irma; Allebes, Wil A.; van der Meer, Arnold; Hilbrands, Luuk B.; Baas, Marije C.; Hack, C. Erik; van Reekum, Franka E.; Verhaar, Marianne C.; et al. (Frontiers in Immunology, 2018)
Individual HLA mismatches may differentially impact graft survival after kidney transplantation. Therefore, there is a need for a reliable tool to define permissible HLA mismatches in kidney transplantation. We previously demonstrated that donor-derived Predicted Indirectly ReCognizable HLA Epitopes presented by recipient HLA class II (PIRCHE-II) play a role in de novo DSA formation after kidney transplantation. In the present Dutch multi-center study we evaluated the possible association between PIRCHE-II and kidney graft failure in 2,918 donor-recipient couples that were transplanted between 1995 and 2005. For these donors-recipients couples, PIRCHE-II numbers were related to graft survival in univariate and multivariable analyses. Adjusted for confounders, the natural logarithm of PIRCHE-II was associated with a higher risk for graft failure (HR:1.13, 95% CI:1.04-1.23, p=0.003). When analyzing a subgroup of patients who had their first transplantation, the hazard ratio of graft failure for ln(PIRCHE-II) was higher compared to the overall cohort (HR:1.22, 95% CI:1.10-1.34, p<0.001). PIRCHE-II demonstrated both early and late effects on graft failure in this subgroup. These data suggest that the PIRCHE-II may impact graft survival after kidney transplantation. Inclusion of PIRCHE-II in donor-selection criteria may eventually lead to an improved kidney graft survival.